1989
DOI: 10.1002/ps.2780260207
|View full text |Cite
|
Sign up to set email alerts
|

Off‐target deposition and drift of aerially applied agricultural sprays

Abstract: OH-target drijl and deposition of aerially applied deltamethrin sprays in an agricultural situation were determined using stainless steel (20 x 40 cm) ground deposit samplers and 'Rotorods'. Off-target spray deposition decreased exponentially with distance in situations where applications were made in winds with speeds equal to, or just above, maximum label limits for aerial application (8 km h-'). The results are compared with those of previous studies. The effectiveness of a 100-m 'no spray' bufSer zone in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…cated. Riley et al 1989 reported a 10-fold decrease in deltamethrin residues at the outer limit of a 100-m buffer zone compared to the edge of the sprayed field. Deltamethrin's registration for aerial spraying requires a 100-m buffer zone around all bodies of water, including wetlands and sloughs.…”
Section: A Entry Into the Environmentmentioning
confidence: 96%
“…cated. Riley et al 1989 reported a 10-fold decrease in deltamethrin residues at the outer limit of a 100-m buffer zone compared to the edge of the sprayed field. Deltamethrin's registration for aerial spraying requires a 100-m buffer zone around all bodies of water, including wetlands and sloughs.…”
Section: A Entry Into the Environmentmentioning
confidence: 96%
“…There have been several previous studies that have addressed aircraft spray drift, for example Yates et al (1978), Akesson and Yates (1974)(p. 92–98), Riley and Wiesner (1989), Richardson et al (1995), and the U.S. Spray Drift Task Force project (Spray Drift Task Force, 1997). Spray drift can pose a potential source of contamination to the environment, unless the application process is effectively managed.…”
mentioning
confidence: 99%
“…Sundaram et al, 1988). Using a model, they predicted that a buffer width of 20 m caused less than 0.02% mortality of Salmo gairdnei rainbow trout in water depths greater than 0.1 m. For aerial application, Riley et al (1989) considered that a 100 m buffer zone would ensure that there would be at least a 10× decrease from the deposit observed at the edge of the target area, even when wind speeds exceed those currently recommended for agricultural sprays. In several countries an untreated buffer zone has been proposed to protect ecologically sensitive areas, especially ponds and streams to prevent a significant impact on fish and their food populations.…”
Section: Aircraft Regulationsmentioning
confidence: 99%